Adverse effects on second-line highly active antiretroviral therapy (HAART) among HIV infected adults and children treated at Mildway Uganda - Namukanja, Phoebe Monalisa-Mayambala (University of Limpopo (Medunsa Campus), 2011)
Background Available and affordable second-line antiretroviral treatment regimens are a key component of universal access to treatment and its continuation. However, providing second-line ART is affected by a number of factors including infrastructure, skills and cod competency of available personnel, cost and availability of second-line drugs. Like first-line antiretroviral agents, second-line drugs have also inherent toxicities. While these have been described in adults, few studies reported this in children. Hence, the need to conduct this study. The aim of the study was to characterize the adverse effects on second-line antiretroviral therapy among HIV infected adults and adolescents and children treated at Mildmay Uganda (MUg). Method This was a cross-sectional study based on the review of patients' records. Data was extracted from client medical charts of patients on second-line antiretroviral treatment regimens treated at Mildmay Uganda Centre from January 2000 to December 2008. Results In total, 247 cases, the majority (90.7%) of the study participants were aged 13 years and above, female (53.0%), and single (68.0%). With regard to reasons that led to the second-line regimen, the main reason for switching was treatment failure (83%), followed by toxicity (5.7%), and other reasons such as the onset of Kaposi Sarcoma disease, maintaining regimen after transfer, and nevirapine pre-exposure. Overall, 55 out of 247 patients suffered from one or more adverse effects, a prevalence of 22.3%. The mean number of adverse drug reactions (ADR) was 1.3 per patient. Of the 55 who experienced adverse effects, 76.4% experienced one type of adverse effect. The three most common adverse effects were gastro-intestinal, followed by hematological and peripheral neuropathy. Based on age, while adults experienced a broad range of adverse 11 drug reactions including metabolic and hepatic ADRs besides the three cited above; children experienced two types only, gastrointestinal, and hematological ADRs. Hematological ADRs were significantly more prevalent in children than adults (66.7% versus 21.4%); they were also more prevalent in females than males (30.8% versus 15.2%). In contrast, while metabolic ADRs were equally distributed, peripheral neuropathy was more prevalent in males than females (30.3% versus 20.5%). Based on the number of ADRs experienced, more males than females (19.8% versus 14.5%) experienced one type of adverse effect whereas more females than males (6.1% versus 4.3%) experienced two to three adverse drug reactions to second-line regimens. Clinically, the didanosine-based regimens were the most associated with ADRs in both children and adults. In Children, the regimen, ABC/DDI/LPV/R, was responsible of 66.7% of ADRs documented; while in adults it was involved in 60.3% of ADRs. Similarly, TDF-, zidovudine-, and stavudine-based regimens were also involved respectively in 52.9%, 17.8%, and 14.7% of ADRs. Based on gender, didanosine-containing regimen, with either TDF or stavudine with lopinavir/r were responsible of 66.7% of ADRs reported in males; while TDF-based regimen with lamivudine or FTC were involved in 21.1% of ADRs also in males. In females, didanosine-, TDF-, zidovudine-, and stavudine-based regimens were also involved respectively in 57.9%, 36.9%, 23.7%, and 7.9% of ADRs. The regimen, TDF/DDI/LPV/R, was also the most associated with the occurrence of ADRs in females as it was in males. Moreover, although no difference was found among patients whose bodyweights increased significantly and those whose did not, patients whose CD4 counts increased significantly experienced more ADRs than those whose had not (8.8% versus 1.3%, p= 0.03). Conclusion Overall, second-line regimens seem to be well tolerated as the overall prevalence of adverse effects was 22.37%. The didanosine-containing regimens were most associated with the occurrence of ADRs. Hematological ADRs were more prevalent in children than 12 adults; and more in females than males. In contrast, while metabolic ADRs were equally distributed, peripheral neuropathy was more prevalent in males than females. These findings emphasize the need to individualize treatment based on the characteristics of the patient.
Thesis (MPH) -- University of Limpopo (Medunsa Campus), 2011.
Keywords: Antiretroviral therapy, highly active